Dietary Acculturation among Puerto Rican Adults Varies by Acculturation Construct and Dietary Measure - Mattei, Josiemer (J Nutr, 2018)
BACKGROUND: The role of acculturation in dietary behaviors among Hispanics/Latinos in the United States remains unclear. Discrepancies may be explained by variations in acculturation constructs or ethnicity-specific dynamics. OBJECTIVE: We aimed to compare relations between 3 different acculturation constructs with dietary quality and patterns among Puerto Ricans in the mainland United States. METHODS: We analyzed cross-sectional data with 1194–1380 Puerto Ricans, aged 45–75 y. Acculturation was measured with the use of a language-based scale (0–100; higher score denotes more English use), a psychological-based scale (0–50; higher score denotes stronger US orientation), and years living in the mainland United States. Diet quality scores (higher scores denote healthier diet) were defined with the use of the Alternate Healthy Eating Index-2010 (AHEI) and the Mediterranean Diet Score (MeDS). Three dietary patterns were previously derived with the use of principal components analysis. Adjusted multivariable regression models tested the association of each acculturation construct with diet quality score or pattern. Interaction terms were included for income or education status. RESULTS: Psychological-based acculturation, but not the other constructs, was positively associated with AHEI (β ± SE: 0.013 ± 0.004; P = 0.002) and MeDS (0.009 ± 0.005; P = 0.041). Income, but not education, moderated this association (P = 0.03), with higher diet quality observed with higher income (>$25,000) and stronger US orientation. All constructs were inversely associated with a traditional dietary pattern, with the language-based scale being stronger (z score β ± SE: −0.160 ± 0.032; P < 0.0001) than the psychological-based scale (−0.097 ± 0.028; P = 0.001) or years living in the mainland United States (−0.058 ± 0.028; P = 0.041). No associations were observed for the Western or sweets/desserts patterns. CONCLUSIONS: In Puerto Rican adults, stronger psychological US orientation was associated with higher diet quality, particularly with higher income. More Spanish use, stronger psychological Puerto Rican orientation, and shorter length of mainland-US residency were associated with traditional dietary patterns. Appropriate diet-related acculturation constructs should be carefully considered among Hispanics/Latinos. This trial was registered at clinicaltrials.gov as NCT01231958.